Development and characterization of porous functionalized collagen scaffolds for delivery of FGF-2 - Pokholenko, Ia.O.; Chetyrkina, M.D.; Dubey, L.V.; Dubey, I.Ya.; Moshynets, O.V.; Sheludko, E.V.; Shpylova, S.P.; Degtiarova, M.I.; Kordium, V.A. (Вiopolymers and Cell, 2014)
Aim. To develop the porous functionalized collagen scaffold for the delivery of FGF-2 and studying its properties in vitro and in vivo. Methods. Porous collagen scaffolds were prepared by freeze- drying collagen I solutions containing the polymer developed on the basis of cross-linked modified heparin. The scaffolds have been analyzed by SEM, AFM and SCLM. The angiogenic activity of these scaffolds loaded with FGF-2 was tested in a CAM assay. Results. The data obtained by SEM and SCLM analysis revealed that the scaffold mainly has a layered structure with pores forming a connection between the layers. The average pore size of the scaffolds varied from 76 to 150 µm. Scaffolds containing the polymer were able to incorporate human FGF-2. Proposed compositions promoted angiogenesis in CAM assay. Conclusions. The developed porous functionalized collagen scaffold incorporating FGF-2 can be used as a vehicle for the sustained delivery of the growth factor both in vitro and in vivo.